Being a Foreigner Among Domestic Banks : Asset or Liability? - Horen, Neeltje (IMF Working Papers; Working Paper ;, 2009)
Studying a large number of banks in various countries between 1999 and 2006, we document that foreign banks perform better when from a high income country, when host country competition is limited, and when they are large and rely more on deposits for funding. Foreign banks' performance improves over time, possibly as they adapt, and is better when the home country is geographical or cultural (but not institutional) close to the host country. These findings show the importance of controlling for heterogeneity among foreign banks and help reconcile some contradictory results found in the literature on foreign banks' performance.